Bibliography: accelerationism - Tinnes, Judith (Perspectives on terrorism, 2022)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on accelerationism — a specific form of anti-government extremism that aims to push the existing socio-political system toward a violent collapse. The compilation focuses on recent publications (up to December 2022) and should not be considered exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.